Coconut in Vietnam: Midrib baskets: The art of giving - Bioversity International (2006)
The information contained in this brochure is from a pilot study carried out in Ben Tre province, Vietnam. The research investigated the marketing chain for gift baskets made from coconut laeves, a high-value coconut product made by local communities in Vietnam. The study focused on marketing strategies used by actors in the market chain and their harvest practices.